Real time interior water and thermal monitoring of fuel cell with micro 3-in-1 sensor. (February 2015) - Lee, Chi-Yuan; Fang, Li-Hsing; Su, Ay; Liu, Yun-Min; Lee, Chung-Ju
Abstract: The operating temperature and internal water accumulation influence the fuel cell performance significantly, and various regions inside the fuel cell still have non-uniformity. At present, only external, invasive, theoretical and simulation methods are available. The real information inside the fuel cell cannot be known instantly. This study used micro-electro-mechanical systems (MEMS) technology to develop a temperature, pressure and flow 3-in-1 micro sensor. First, the PI foil (Polyimide foil, 50 μm thick) was used to develop a 3-in-1 micro sensor, and then the 3-in-1 micro sensor was embedded in the low-temperature fuel cell for real-time microscopic monitoring of internal temperature, pressure and flow of fuel cell. In terms of temperature inside the fuel cell, as the upstream and midstream formed heat can be carried away by sufficient gas at the inlet, and the downstream reaction is violent, the downstream temperature is higher than upstream and midstream temperatures. In terms of pressure, in long-term observation, the internal pressure fluctuates, the pressure increases momently and reverts at some time points. This is possibly due to the removal of accumulated water from the flow channel. In terms of flow, the flow supplied by flow controller is higher than the upstream and downstream micro flow sensors, and the difference matches the gas leakage value. Highlights: This study first used MEMS technology to develop a 3-in-1 micro sensor. Micro sensors for real-time monitoring internal information of fuel cell. Micro sensor has three functions, small size and quick response.